(untitled) (Journal of Academic Finance, 2024)
Purpose: Imagine control configurations within SMEs in Cameroon as a vibrant tapestry, intricately woven with various threads of managerial practices and systems. The aim of this work is to unravel this tapestry and shed light on the interconnected elements that constitute control configurations in the context of SMEs in Cameroon. Method: This study is exploratory and thus, follows a qualitative/abduction approach to explore an uncover control practices and contextual variables in SMEs in the Cameroon context and to understand the way they interact in a package. The population of our study is made up of top management team (general managers or chief executive officers, internal and external accountants, management controllers, financial and operational managers) of SMEs in Cameroon. Therefore, semi structured interviews were used on 25 top management teams from 20 SMEs in the cities of Douala, Bafoussam and Bamenda for data collection. Data collected were analysed using the Qualitative Comparative Analysis, a set theoretic method designed to compare multiple cases in terms of complex configurations of attributes and outcomes. NVivo 12 and fsQCA software were used as data analysis tools. Findings: From the analysis, findings revealed six control configurations used by top managers in the Cameroon SMEs labelled as holistic, soft-driven, police-based, semi engaged, mechanistic and formation. Originality: This study is one of the first in the SME context in Africa. This work explores and uncover the configuration of management control systems operating as a package in SME that leads to superior performance.